Magnetic Correlation Engineering in Spin‐Sandwiched Layered Magnetic Frameworks. Issue 70 (16th November 2020) - Fukunaga, Hiroki; Kosaka, Wataru; Nemoto, Honoka; Taniguchi, Kouji; Kawaguchi, Shogo; Sugimoto, Kunihisa; Miyasaka, Hitoshi
Abstract: The insertion of "sandwiched spins" between magnetic layers could efficiently affect the interlayer magnetic correlations, but doing so increases the complexity in the interlayer spin alignment because of competition between the inserted spin‐layer interaction J NNI and the interlayer through‐space interaction J NNNI if the magnitude of J NNI is of the same order as J NNNI with reciprocal signs of the respective interactions. Herein, systematic tuning of the magnetic phase variations by J NNI and J NNNI in two kinds of metal‐variable isostructural series of supramolecular pillared layer magnets [MCp*2 ][{Ru2 II, II (2, 3, 5, 6‐F4 CO2 )4 }2 (TCNQ)]⋅ 2 DCE (M=Co, Fe, Cr; 2, 3, 5, 6‐F4 PhCO2 − =2, 3, 5, 6‐tetrafluorobenzoate; TCNQ=7, 7, 8, 8‐tetracyano‐ p ‐quinodimethane; DCE=1, 2‐dichloroethane) and their DCE‐free series, in which [MCp*2 ] + (Cp*=η 5 ‐C5 Me5 ) species with S= 0, 1/2, and 3/2 for M=Co, Fe, Cr, respectively, are sandwiched between ferrimagnetic layers of [{Ru2 }2 (TCNQ)] −, is demonstrated. The results showed that the flexible magnetic natures of these magnets are changeable in dependence on J NNI and J NNNI, as well as on interlayer inserted spins M. Abstract : Magnetic sandwiches : What happens in a spin‐sandwiched layered magnet when the sandwiched spin is altered? Herein, this question was answered for two series of isostructural compounds by changing [MCp*2 ] + spins sandwiched between ferrimagnetic layers of [{Ru2 }2 (TCNQ)] − . The magnetic phase can be described as a competition between the interlayer magnetic interaction and the layer⋅⋅⋅ [MCp*2 ] + interaction, which were tuned by solvation/desolvation and by changing M among Co, Fe, and Cr, respectively. Cp*=pentamethylcyclopentadienyl, TCNQ=7, 7, 8, 8‐tetracyano‐ p ‐quinodimethane